Mucocele of the appendix: A comprehensive case report and literature review - Bhaskar Jyoti Neog; Subodh Gupta; V. K. Rastogi; Paras Passi (Indian Journal of Community and Family Medicine)
Appendiceal mucocele, a rare condition characterized by the accumulation of mucus in the appendix, presents a diagnostic challenge due to its nonspecific clinical features. We present the case of a 60-year-old female with recurrent right lower quadrant abdominal pain, nausea, and anorexia, suggestive of appendicular origin. Abdominal ultrasound revealed a hypoechoic cystic mass, prompting further investigation with magnetic resonance imaging (MRI), which confirmed an inflamed appendix. Exploratory laparotomy revealed a retroperitoneal cavity containing mucous gelatinous material, indicative of a mucocele. Histopathological examination confirmed extensive mucosal sloughing, neutrophilic infiltrate, lymphoma cells, and muciphages, along with areas of dystrophic calcification and fibrosis. The patient recovered postoperatively and remained symptom-free during follow-up. Appendiceal mucocele poses a diagnostic challenge due to its variable presentation and resemblance to other abdominal pathologies. Radiological imaging plays a crucial role in diagnosis, with abdominal ultrasound and MRI aiding in preoperative evaluation. Surgical resection remains the cornerstone of management, with laparotomy preferred to avoid mucocele rupture.